2003
DOI: 10.1159/000071089
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Study of Combined Visual Laser Ablation and Transurethral Resection of the Prostate versus Transurethral Prostatectomy Alone

Abstract: Introduction: Visual laser ablation of the prostate (VLAP) has a clinical failure rate of up to 18% which is 3 times higher than transurethral resection of the prostate (TURP) alone. Prolonged spontaneous passage of necrotic debris is the major shortcoming of this method. Therefore combined visual laser-assisted and transurethral prostatectomy was compared to TURP alone. Materials and Methods: 105 patients were evaluated in a prospective randomized study comparing TURP alone and VLAP combined with TURP. The pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…In two large clinical trials, an average symptom improvement of 61% at 12 months has been reported [19]. Results of randomized trials comparing visual laser ablation of the prostate (VLAP) with TURP have confirmed the satisfactory clinical outcome of the laser procedure [15,[20][21][22][23][24][25][26]. Peak flow rates increased by 93% 12 months after VLAP compared with 109% after TURP.…”
Section: Visual Laser Ablation Of the Prostatementioning
confidence: 92%
“…In two large clinical trials, an average symptom improvement of 61% at 12 months has been reported [19]. Results of randomized trials comparing visual laser ablation of the prostate (VLAP) with TURP have confirmed the satisfactory clinical outcome of the laser procedure [15,[20][21][22][23][24][25][26]. Peak flow rates increased by 93% 12 months after VLAP compared with 109% after TURP.…”
Section: Visual Laser Ablation Of the Prostatementioning
confidence: 92%
“…The applications are repeated systematically and with overlap until all visible obstructing prostatic tissue has been coagulated [14]. Results of randomized trials comparing visual laser ablation of the prostate (VLAP) with TURP have confirmed the satisfactory clinical outcome of the laser procedure [15,[20][21][22][23][24][25][26]. Coagulated tissue eventually will necrose and slough within weeks or months, often accompanied by bothersome irritative voiding symptoms [3,[15][16][17][18].…”
Section: Visual Laser Ablation Of the Prostatementioning
confidence: 99%
“…After surgery, urinary retention and the need for long-lasting catheterization rate are still the drawbacks. Postoperative irritative voiding symptoms due to late sloughed off necrotic tissue makes VLAP not succeed in replacing TURP [4,5]. A high retreatment rate of 1.8% to 38% was also reported by Muschter [6].…”
Section: Introductionmentioning
confidence: 96%